Iloilo City University student's perception on the characteristics of an admired leader an element of change in the Philippines' political arena - Alojado, Darhlyn S.; Balinas, Christine Joy D.; Cabrias, Glenah Marie C.; Pacheco, Diane Irish G.; Segudine, Ruth Abigail M.
The study intends of determining the university students' perceptions on the characteristics of an admired leader especially political leader that they should possess in leading every nation's affair. Proper determination of characteristics of a leader is of great help in deciding who is to vote in the upcoming 2010 election. Moreover, the study reviews the schools participation in developing leadership potentials among its students. A total of 105 respondents were selected from 7 universities in Iloilo City. The seven universities includes two government-subsidized institutions: the University of the Philippines Visayas (est. 1948), and the West Visayas State University (est. 1902) ; the six private universities : the catholic, University of San Agustin (est. 1904), the protestant, Central Philippine University (est. 1905), the secular and Lopez-owned University of Iloilo (est. 1947) and the catholic, St. Paul University (est. 1946) ; and the maritime university: the John B. Lacson Maritime Foundation University. Fifteen students were made use as respondents from each every university. The review and analysis of university students' perceptions reveal that students preferred a candidate with characteristics such as excellent educational background, effective administrative skills, good family background, ability to listen and relate to people, possess good communication skills, good spiritual foundation, empathy to people, ability to find the right people for cabinet positions, aware and take actions on environmental issues, and encourager and charismatic inspirer. This only shows that the young bloods nowadays preferred the personal value of a person to them than those qualities that relates to economical foundation of a person. In addition, many youths nowadays are becoming more Nationalistic than before evidenced by their actual participation in the administrative government at present.